ASUPAN ENERGI, ASUPAN KARBOHIDRAT DAN KADAR GLUKOSA DARAH PASIEN RAWAT INAP DIABETES MELITUS TIPE 2 DI RSUD KOTA SALATIGA - Sandra H, Rachel Anindya; Isnawati, Mufliah (Poltekkes Kemenkes Semarang, 2015)
Background: Non-communicable diseases (PTM) that take up a lot of attention are Diabetes Mellitus (DM). In Central Java, the percentage of cases of DM in 2012 was 15.8%. DM is a disorder caused by inadequate insulin hormone or impaired insulin function and cannot control blood sugar levels. Excess high energy intake of other excess nutrients, one of which is storage and can increase blood sugar levels. The pattern of DM diet in Salatiga City Hospital is adjusted to the cost of food (unit cost) of each treatment class. Differences in diet in each class consider the difference in the amount of energy and carbohydrates that are not according to needsObjective: to determine the effect of various differences in the composition of rice flour and black bean flour red against the fiber content and the received power snack bar.Methods: The research subjects were patients with a medical diagnosis of type 2 diabetes mellitus who were hospitalized in the VIP, I, II, III care class, over 18 years of age and were not fasting. Type of descriptive-analytic research and cross-sectional study design. How to take non-probability sampling. Data collected included blood glucose levels, energy intake, carbohydrate intake (Comstock method), calculation of energy and nutrient requirements. Statistical analysis uses Pearson Correlation and Linear Regression.Results: The research subjects were patients with a medical diagnosis of type 2 diabetes mellitus who were hospitalized in the VIP, I, II, III care class, over 18 years of age and were not fasting. Type of descriptive-analytic research and cross-sectional study design. How to take non-probability sampling. Data collected included blood glucose levels, energy intake, carbohydrate intake (Comstock method), calculation of energy and nutrient requirements. Statistical analysis uses Pearson Correlation and Linear Regression.